Effect of consuming sodium bicarbonate on the numeric value of the accumulation of lactic acid levels in the blood after maximum physical effort between gymnastics and judo players - Majid, Salih; kadhim, Mohammed (Journal of Physical Education, 2012)
The purpose of the research was to study the antacids that make blood baseline and impact to keep the blood’s ability to absorb acidic without access to the collapse of the blood and turn to Alhmouzh. So, the researchers on the study combines lactic acid and factors affecting decreased for use in training and legally lead the body to take advantage of it and the speed to get rid of it and carry large amounts of this acid in the blood.Sample consisted of players gymnastics’s (10) players and players of judo’s (10) players who are competing in the same weight (60) kg as selected way intentional they have the same old training, has researchers conducted a test of equal and smoothing sample in a variable concentration lactic acid at rest, age and weight training.The laboratory Im walking average for the purpose of warming up and Althau to work muscular appropriate then instruct the researcher to the lab to lift the rhythm by pressing the appropriate button to the level that has been stored for the purpose of access to a trot on Altrid miles and running for five minutes effort on high of (175) z / minutes according to what came from the experience reconnaissance and take advantage of determining intensity required for the research sample. then the researcher after the completion of the running for five minutes to give everyone a break on be measuring and twitching thumb left after every minute of rest starting from the end of the effort directly for nine minutes Full and record the results extracted. After giving a period of 5 days of rest negative are re-test, but this time is a dose of a substance sodium bicarbonate and by (0.03) grams per kilogram of body weight in a glass (250) ml of water for each player before working radios complete. For the purpose of controlling variables extraneous and influential in the experiment were given sample breakfast similar (boiled egg with a loaf of bread with one teaspoon and a half of sugar in a glass of tea) before the experiment test three hours after two hours of breakfast was addressed substance sodium bicarbonate and thus eating material sodium bicarbonate accompanied by lemon flavor to accept sample an hour before the test.Conclusions:1 - low concentration of lactic acid immediately after the performance.2 - begins lactic acid concentration to rise after the first minute of rest unprecedented performance.3 - lactic acid concentration rises regularly after the performance, but after four to five minutes, urges the flow of blood Laktic bringing Turkish significantly.4 - up lactic acid concentration to peak at the eighth minute and then begins to fall after that.5 - the behavior of the blood was similar in the process of getting rid of lactic acid compound even after taking sodium bicarbonate.6 - eating sodium bicarbonate reduces the concentration of lactic acid in the blood.7 - delay taking sodium bicarbonate from the point of the collapse of the blood towards acidity (rapid ascent of the blood concentration).8 - the similarity of behavior of blood in both my sample search when dealing with sodium